Pengaruh Harga Diri terhadap Ide Bunuh Diri Mahasiswa Aktif Strata Satu Fakultas Ilmu Pendidikan dan Psikologi Universitas Negeri Manado Tahun Ajaran 2024/2025 - Manoa, Debora G. Deakoni; Mandang, Jofie Hilda; Kapahang, Gloridei Lingkanbene (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
Pusat Informasi Kriminal Nasional Badan Reserse Kriminal Kepolisian Republik Indonesia shows that all suicides in Indonesia throughout the year have continued to increase by 60% in the last five years. North Sulawesi is the fourth province with the highest crude suicide attempt rate base on The Lancet Regional Health – Southeast Asia. This study aims to analyze the effect of self-esteem on suicidal ideation of active undergraduate students of the Faculty of Education and Psychology Universitas Negeri Manado academic year 2024/2025. The research design was quantitative with a total research sample of 308 active undergraduate students of the Faculty of Education and Psychology, Universitas Negeri Manado, aged 15 to 29 years old who were determined using incidental sampling techniques. Data collection was done by distributing questionnaires consisting of self-esteem and suicidal ideation scales which were then analyzed with the help of SPSS. The results of simple linear regression analysis show that if self-esteem is fixed, it will increase suicidal ideation by 41.895 units. Meanwhile, if self-esteem increases by one unit, there will be a decrease in suicidal ideation by 0.202. The results showed a significance value of 0.000 so it was proven that self-esteem had a significant effect on suicidal ideation. The ability of self-esteem to explain variations in suicidal ideation is 23.9%. The results of this study prove the effect of self-esteem on suicidal ideation of active undergraduate students of the Faculty of Education and Psychology, Universitas Negeri Manado academic year 2024/2025.